Sexual dysfunctions in schizophrenia: Beyond antipsychotics. A systematic review - Dumontaud, Marion; Korchia, Théo; Khouani, Jérémy; Lancon, Christophe; Auquier, Pascal; Boyer, Laurent; Fond, Guillaume (Progress in neuro-psychopharmacology & biological psychiatry, 2020)
Sexual dysfunctions (SD) in schizophrenia are frequent with strong impact on adherence and quality of life. Current recommendations stipulate to switch to prolactin-sparing antipsychotic in case of SD. To synthetize in a systematic review data on the SD prevalence and the associated risk factors in schizophrenia (SZ). Medline, Google Scholar, PsychInfo, and Cochrane were explored, without any year or language restriction. Overall, 89 studies and 25,490 participants were included in the present review. SZ subjects aged 18–70 reported high SD frequency [30%–82%] (men [33%- 85%]; women [25%- 85%]). For SZ men erectile dysfunction [31%–95%] was the most frequent SD vs. loss of libido for women [31%–100%]. The following risk factors were associated with increased SD: 1. Illness severity (including psychotic symptomatology, early age at SZ onset, negative symptomatology, and continuous illness course), 2. Depressive symptomatology 3. Antipsychotics (especially first generation antipsychotics, risperidone and antipsychotic polytherapy). Switching to prolactin-sparing antipsychotics has shown effectiveness in some studies (especially aripiprazole). Antidepressants were not found to be associated with SD in SZ subjects. The prevalence of SD is high in SZ subjects. In addition to the current guidelines, the present review suggests that treating depressive symptoms may be a major intervention to improve SD in SZ subjects. Sociodemographic variables, physical illnesses, metabolic syndrome and peripheral inflammation have been poorly or never explored and should be included in future studies. •subjects with schizophrenia aged reported high sexual dysfunctions (SD) frequency.•For men erectile dysfunction was the most frequent SD vs. loss of libido for women.•psychotic and negative symptomatology, early age at SZ onset, and continuous illness course were associated with increased SD risk•Depressive symptomatology was also associated but poorly explored•Switching to prolactin-sparing antipsychotics has shown effectiveness (especially aripiprazole).•treating depressive symptoms may be a major intervention to improve SD in SZ subjects.•physical illnesses, metabolic syndrome and peripheral inflammation have been poorly or never explored.